An evidence-based model to promote community engagement in health intervention research: the Quiet 4 Healthy Farm experience - McCullagh, Marjorie C. (Frontiers in Public Health, 2025)
Community engagement involves working collaboratively with groups of people on issues affecting their well-being. The process is central to public health. Although the concept of community engagement is based on the assumption that active participation by community residents in the process of improving health and social outcomes will lead to an empowered community, and long-term health and social improvements, there is little research on how to achieve community engagement. This article describes a variety of the author’s practices in community engagement in the context of community-based health promotion intervention research. The practices highlighted in this perspective are highly adaptable to other studies, participants, settings, and health issues, and have potential for augmenting the community engagement and success of future community-based health behavior studies, and consequently contribute to the public health.